A European, multicentre, observational, post-authorisation safety study of oral sulphate solution: compliance and safety - Regula, Jaroslaw; Spaander, Manon C.W., MD; Suchanek, Stepan; Kornowski, Anne; Perrot, Valerie; Fischbach, Wolfgang; the DUS investigators (Endoscopy International Open, 2020)
Background and study aims Oral sulphate solution (OSS) is a sulphate-based, low-volume bowel cleansing preparation taken in two doses of 500 mL, each followed by 1000mL of water or clear liquid. The primary objective of this observational study was to document compliance with the recommended hydration guidelines in a representative sample of the European population. Patients and methods Prospective, non-interventional, multicentre study (NCT02630680, EUPAS9361) in patients prescribed OSS for colonoscopy preparation in routine clinical practice in Europe. Patients were included according to pre-agreed consecutive enrolment rules. Patients recorded the volume of OSS and water or clear liquid intake, and occurrence of adverse events (AEs). Compliance with hydration was calculated as a ratio of actual volume of water/clear liquid taken versus prescribed 2,000 mL, and non-compliance defined as < 75 % intake. Colon cleansing level was assessed on a 4-point scale. Results Between October 2015 and January 2017, 1,281 patients were recruited in 16 centres in four European countries (safety population n = 1,206; registry population n = 1,177). Of patients, 94.5 % were ≥ 75 % and 86.8 % 100 % compliant with hydration guidelines. Patients took an average of 96.8 % of the recommended OSS volume; 46 patients (3.9 %) were non-compliant. Colon cleansing levels were good-to-excellent in 87.6 % of patients. Three hundred and twenty-nine patients (27.3 %) experienced 758 treatment-related AEs, mostly gastrointestinal (82.9 %), all were mild-to-moderate. Non-compliant patients had no AEs suggestive of dehydration.Conclusion In this non-interventional study in a real-life setting, treatment compliance with hydration guidelines was good-to-excellent in 94.5 % of patients receiving OSS. The safety profile of OSS was similar to the prescribing information. TRIAL REGISTRATION: Observational study EUPAS9361 at www.encepp.eu